The accessibility and safety of inserting proximal basilic and axillary veins central lines in neonates - Hany Aly; Mohamed Mohamed; Sehar Ejaz; Mohsen A A Farghaly; Komail Malik; Ibrahim Qattea (SAGE Open Medicine, 2023)
Objectives: to evaluate the accessibility, success rate, and attributable complications and to describe the maneuver for central line insertion via proximal basilic or axillary veins in neonates. Methods: This retrospective study included all infants admitted to the neonatal intensive care unit and had an axillary central line inserted or attempted. Success rate, complications, and outcomes were reviewed. Results: Axillary central line was attempted in 85 infants and was successful in 78 infants with a success rate of 91.7%. The median postnatal age of patients was 8 days (2 days–92 days), and the median weight of patients at the procedure was 2600 g (590 g–3900 g). The median corrected gestational age of patients at the procedure was 36 weeks (23 weeks–46 weeks). No serious complication was observed in any of the 85 infants. Conclusion: This study demonstrated a high success rate for insertion of proximal basilic and axillary veins central lines in neonates with difficult vascular access. This procedure was feasible in very low birth and extremely low birth preterm infants, especially in those who failed previous central line attempts.